2017
DOI: 10.1002/bjs.10498
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and mortality 1 year after major non-cardiac surgery

Abstract: Although the majority of postoperative AKI was mild, there was a strong association with risk of death in the year after surgery. Underlying decreases in serum creatinine concentration after major surgery could lead to underestimation of AKI severity and overestimation of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 30 publications
10
77
2
Order By: Relevance
“…Patients were classified as having persistent AKI if the last postoperative serum creatinine level measured up to and including 30 days after surgery was at least 50 per cent greater than the preoperative baseline12. Major complications were defined as Clavien–Dindo grade III–V complications13, which include unplanned procedures under local or general anaesthesia, organ support in an intensive care setting, stroke or death.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were classified as having persistent AKI if the last postoperative serum creatinine level measured up to and including 30 days after surgery was at least 50 per cent greater than the preoperative baseline12. Major complications were defined as Clavien–Dindo grade III–V complications13, which include unplanned procedures under local or general anaesthesia, organ support in an intensive care setting, stroke or death.…”
Section: Methodsmentioning
confidence: 99%
“…AKI classified based on postoperative sCr increase within the first three postoperative days was a rare condition and was not related to mortality. AKI defined by KDIGO based on sCr changes within the 7 days after surgery has been shown to be related with increased mortality in orthopedic patients and in major noncardiac surgery . According to our results, it appears that patients’ preoperative kidney function has much more effect on outcome than do changes occurring during the short, rather stable and well‐monitored perioperative period.…”
Section: Discussionmentioning
confidence: 56%
“…However, concerns over their safety profile after colorectal surgery persist [32]. The nephrotoxic effects of NSAIDs after non-cardiac surgery are well understood and, whilst commonly mild, are associated with 1-year postoperative mortality [17]. More recently, data from large, prospective databases have identified an association between NSAIDs and anastomotic leak, although this finding is inconsistent [15,16].…”
Section: Discussionmentioning
confidence: 97%
“…Randomized clinical trials (RCTs) of non-steroidal antiinflammatory drugs (NSAIDs) have demonstrated significant improvements in gastrointestinal recovery, probably through their anti-inflammatory and opioidsparing properties [13,14]. Although NSAIDs appear to offer effective postoperative analgesia, concerns remain over their safety, including the risk of AKI and anastomotic leak [15][16][17].…”
Section: Introductionmentioning
confidence: 99%